Sexual-dimorphism in human immune system aging - Eladio J. Márquez (Nature Portfolio, 2020)
Whether the immune system aging differs between men and women is barely known. Here the authors characterize gene expression, chromatin state and immune subset composition in the blood of healthy humans 22 to 93 years of age, uncovering shared as well as sex-unique alterations, and create a web resource to interactively explore the data.